149k views
5 votes
What is (f−g)(x)?

f(x)=3x^5+6x^2−5
g(x)=2x^4+7x^2−x+16

Enter your answer.
(f−g)(x)=

User Jeltok
by
5.2k points

1 Answer

6 votes

Answer:


\large\boxed{(f-g)(x)==3x^5-2x^4-x^2+x-21}

Explanation:


(f-g)(x)=f(x)-g(x)\\\\\text{We have}\\\\f(x)=3x^5+6x^2-5\\\\g(x)=2x^4+7x^2-x+16\\\\\text{substitute:}\\\\(f-g)(x)=(3x^5+6x^2-5)-(2x^4+7x^2-x+16)\\\\=3x^5+6x^2-5-2x^4-7x^2+x-16\\\\\text{combine like terms}\\\\=3x^5-2x^4+(6x^2-7x^2)+x+(-5-16)\\\\=3x^5-2x^4-x^2+x-21

User JiajiaGu
by
5.6k points